Performance, incidence of metabolic disturbances and endocrine variables of food-restricted male broiler chickens - Gonzales, E.; Buyse, J.; Loddi, M. M.; Takita, T. S.; Buys, N.; Decuypere, E. (Carfax Publishing, 1998)
1. This experiment was carried out to evaluate the productive and physiological consequences of a slight but long term food restriction of male broiler chickens from 2 commercial strains.2. Cobb-500 and Ross chickens were submitted to a 20% food restriction from 8 to 21 d of age. Strain, food programme and their interactive effects were analysed in terms of consequences upon performance, mortality, incidence of sudden death syndrome (SDS) and ascites syndrome (AS), index of right cardiac hypertrophy and plasma concentrations of hormones related to metabolism and growth (T-3, T-4, T-3:T-4 ratio, IGF-I and GH).3. Although some catch-up growth was observed by refeeding previously restricted birds after 22 d of rearing, food restriction decreased (P less than or equal to 0.05) body weight at market age (42 d) irrespective of the strain, but improved (P less than or equal to 0.05) food conversion.4. The incidence of mortality was not high in non-restricted birds but SDS and AS caused more than 50% of deaths. Hypertrophic cardiac index was observed in chickens of both strains after 4 weeks of age and was higher in ad libitum fed birds.5. During the period of food restriction, plasma T-3 and IGF-I concentrations decreased whereas plasma T-4 and GH concentrations increased compared to those of the age-matched ad libitum fed counterparts. During the subsequent ad libitum feeding period, few differences in circulating hormone concentrations were observed, except for the higher mean CH litres in previously food-restricted chickens at 35 d of age.6. These results indicate that even a non-severe food restriction negatively affects body weight of 42-d-old male broilers but these are benefits with improved food efficiency and diminished mortality from metabolic disturbances. The hormone results suggest that the degree of food restriction applied was not severe because there was a very fast adaptive response with small and transient alterations in T-3, T-4 and GH plasma concentrations during the period of compensatory growth.